2009
DOI: 10.1242/jcs.048926
|View full text |Cite
|
Sign up to set email alerts
|

Wif-1 is expressed at cartilage-mesenchyme interfaces and impedes Wnt3a-mediated inhibition of chondrogenesis

Abstract: Supplementary material available online at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
104
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 98 publications
(110 citation statements)
references
References 72 publications
6
104
0
Order By: Relevance
“…The results of the present study demonstrated that WIF-1 expression is predominantly detected in the superficial layers of articular cartilage. These results are consistent with previous studies which have demonstrated that WIF-1 is highly expressed in the superficial layers of epiphyseal cartilage in bone and tendons (11,12,18). Since WIF-1 is predominantly expressed in articular cartilage, and in bone to a lesser extent (12,18), the present study aimed to investigate whether WIF-1 is upregulated in patients with OA.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results of the present study demonstrated that WIF-1 expression is predominantly detected in the superficial layers of articular cartilage. These results are consistent with previous studies which have demonstrated that WIF-1 is highly expressed in the superficial layers of epiphyseal cartilage in bone and tendons (11,12,18). Since WIF-1 is predominantly expressed in articular cartilage, and in bone to a lesser extent (12,18), the present study aimed to investigate whether WIF-1 is upregulated in patients with OA.…”
Section: Discussionsupporting
confidence: 92%
“…A previous study demonstrated specific binding of WIF-1 to Wnt3a, Wnt4, Wnt5a, Wnt7a, Wnt9a and Wnt11 (18). Furthermore, it has been demonstrated that WIF-1 is capable of blocking Wnt3a-mediated activation of the canonical Wnt signalling pathway, which is associated with cartilage degeneration (18). The results of another previous study demonstrated that WIF-1 was capable of attenuating the CTGF-dependent induction of cartilage matrix gene expression, including aggrecan and COL2A1, in primary murine chondrocytes (11).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…41 This notion seems well supported by other studies, which suggest that Wnt3a can prevent or inhibit chondrogenesis, while Wnt5a supports cartilage formation, but can impede Col2 expression and induce dedifferentiation. 39,42,43 These findings support the Wnt expression trends observed in our data, where both Wnt3a and Wnt5a were expressed in earlier stages following proliferation and FGF-2 supplementation but, following chondrogenic differentiation, Wnt3a and Wnt5a mRNAs and proteins were either significantly decreased or undetected. This expression is likely important in maintaining the ''stemness'' of the SDSCs, which may promote successful responses to chondrogenic media, as well as later expression of Col2, aggrecan, and greater GAG deposition.…”
Section: Discussionsupporting
confidence: 89%
“…WNT5A stimulates the production of several inflammatory cytokines and chemokines, such as IL6, CXCL1, and CXCL8. WNT5A also binds to several members of the Frizzled receptor family, including FZD5 ( Jung, 2013), and is inhibited by WIF1 (Surmann-Schmitt et al, 2009). FZD5 was upregulated and WIF1 was downregulated in our analysis.…”
Section: Figmentioning
confidence: 56%